Pengelolaan Laboratorium Bahasa di Sekolah Menengah Pertama (SMP) Negeri 11 Muaro Jambi - Ubaidillah Ubaidillah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This research is the management of language laboratory in Junior High School (SMP) Negeri 11 Muaro Jambi. This study aims to find the management of language laboratories in Sekolah Mengengah Pertama (SMP) Negeri 11 Muaro Jambi with scope and management functions including management, organizing, implementation of management programs and supervision and utilization of language laboratory management in junior high school (SMP) Negeri 11 Muaro Jambi and analyzing the main functions and tasks of language laboratory managers as well as analyzing inhibitory factors and efforts conducted by SMP Negeri 11 Muaro Jambi. This research method uses qualitative approach, while from the scientific aspect use management approach to see planning, implementation and supervision activities. The findings in the field found that the management of language laboratories in Sekolah Mengengah Pertama (SMP) Negeri 11 Muaro Jambi to the management function in the management of language laboratory equipment has not been optimal, this can be seen from the planning, budgeting, procurement, storage and distribution, use, maintenance and inventory and recording of the management of language laboratories that have not been properly planned, unstructured and organized organized d Well, the implementation of language laboratory management programs has not been carried out optimally supervision and utilization of language laboratory management has not been implemented professionally. From the findings and discussion of research on the management of language laboratories in SMP N 11 Muaro Jambi, it can be concluded that the management of language laboratories applied by SMP N 11 Muaro Jambi in general has not been optimal, especially towards the implementation of the functions and duties of school managers have not been implemented properly. This can be seen in the documentation (data) related to planning, budgeting, procurement, usage, maintenance and inventory has not been carried out optimally